THE USE OF MOBILE -ASSISTED LANGUAGE LEARNING IN EFL TEACHING AND LEARNING: PRACTICES AND READINESS - Maria Septania U. Neto; Derviana Mutiara; Putu Chris Susanto (Seminar Ilmiah Nasional Teknologi, Sains, dan Sosial Humaniora (SINTESA), 2020)
ABSTRACTThe aims of this study; a) to find out how EFL students and teachers use their smart devices and b) to find out the students' readiness of using Mobile Assisted Language Learning (MALL). This study to widespread use of mobile phones and portable devices it is inevitable to think of Mobile Assisted Language Learning as a means of independent learning in Higher Education. In Mobile Learning, devices like smartphones, iPod, tablet, laptop, iPad are implemented to scaffold language learning. This paper focuses on the classification of mobile apps based on primary, secondary and tertiary learners. This research uses descriptive method that aims to describe all responses given by students through given a list of questions. These studies also discussed the design, method, theory and pedagogical features that underpin the current mobile apps. Since these apps are developed to enhance the language skills of the learners, emphasis should be primarily made on the acquisition of language skills such as listening, speaking, reading and writing skills through mobile technology. Thus, the finding showed that the students have positive attitude toward MALL. All the students have smartphone to support the educational purposes inside and outside classroom.Keywords: Mobile assisted language learning (MALL), Primary, secondary and tertiary learners.